STUDENTS ACHIEVEMENT GOALS GENDER DIFFERENCES - Dudkina, Aija; Klekmane, Kristiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This research is the theoretical and practical analysis about achievement goals students gender differences. Theoretical backround contains a review of best-known and the most actual theories about the achievement goals. Aim of the research is theoretical basis and practical research to investigate: Is there any gender differences in achievement goals for students? Methods of the research: demographic questionnaire and Andrew J. Elliot and Kou Murayama and Reinhard Pekrun (2011) „A 3x2 achievement goal questionnaire (AGQ). Research participants is a total of 143 students (71 male and 72 female). Participants were at age range 18 – 25 years (M = 21.25). Male age range were 18 – 25 years (M = 21.90), female age range was 18 – 24 years (M = 20.61). The research results answered to research question "is there any gender differences in achievement goals for students?" has confirmed partly – diferences in scale task-avoidance goals are statistically important (t = 3,546; p < 0.01). Research question has confirmed partly. There are statistically imoprtand gender differences in task-avoidance goals (p < 0.01), but there aren’t any differences in other achievement goals.